EDUKASI BAHAN-BAHAN YANG MENGANDUNG FLOUR DALAM KESEHATAN GIGI DAN MULUT DI MADRASAH IBTIDAYAH (MI) WILAYAH KELURAHAN KELAYAN TENGAH - M Bahrul Ilmi (Jurnal Buletin Al-Ribaath, 2018)
ABSTRACTOne of the causes of high caries sufferers in teeth is the low awareness of patients in checking themselves find out the symptoms, causes and prevention of dental caries. Some of the methods of prevention of dental caries include flouridation of drinking water, flouridation of salt, milk fluid flouridation, healthy dietary improvement, individual action of gargling F, fluorine tablets, brushing with fluid F. The purpose of this dedication is to increase knowledge, understanding, use and benefits of flour-containing substances in the body, as well as prevention of dental caries and knowledge and proper tooth brushing. The method undertaken in this dedication activity is the method of lecture / counseling, namely the provision of information (education) either from pamphlets or videos about materials, uses and benefits as well as understanding the flour itself. Target in this service activity is the students of class V-VI because in this class group have / have permanent teeth, which more susceptible suffering dental caries in order to maintain healthy tooth and mouth early also give education to the surrounding environment. This dedication activity is held from August 2017 to January 2018. It is hoped that with this dedication activity, students of MI will know more about the information about the ingredients, the use and the benefit and the understanding of the flour itself so as to reduce or avoid dental caries disease.Keywords: Education, flour, prevention of dental caries, students of MI.